ANALISIS PENYELENGGARAAN TAMAN BACA MASYARAKAT DALAM MENINGKATKAN KEMAMPUAN MEMBACA DIPELAJARAN BAHASA INDONESIA SISWA KELAS 5 SDN CAGEUR KECAMATAN DARMA - Aulia, Elsa; Nunu Nurfirdaus; Heti Triwahyuni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to find out the factors of low interest in reading in SDN cageur, especially to grade IV (four) students in Indonesian language subjects and to analyze the cageur community reading park in increasing reading interest in cageur students, especially grade IV (four) students in Indonesian language subjects. This study uses a type of qualitative research with a descriptive approach. The data collection techniques used are interviews, observations, and documentation, the information in this research is class teachers and grade IV Indonesian language teachers, grade IV students, school principals, and managers of the Ceager Village Community Reading Park. The results of this study show that the factors of low interest in reading grade IV students of SDN cageur in Indonesian language subjects are lack of awareness of the importance of reading, school libraries that are not qualified, the role of parents is still lacking, and the influence of smartphones. The activities carried out by the community reading park of Cageur Village in improving the reading quality of elementary school children in Cageur Village, especially grade IV children in the Indonesian language subject, are opening free book reading stalls, reading while playing, reading while storytelling, as well as school entrance books and other supporting activities.